Digital Dilemmas: Evaluating the Ethics and Efficacy of Personalised Political Advertising in Modern Democracies - Václav Moravec; Nik Hynek; Beáta Gavurová; Matúš Kubák (Communication Today, 2025)
This study explores the realm of personalised political advertising, examining societal perspectives on clear regulation, enhanced transparency, and empowerment in the digital media sphere. Analysing existing international literature and responses from our own unique survey of 1,213 participants in the Czech Republic, it provides a detailed picture of public perceptions towards the customisation of political messages and control over online content. Findings indicate a significant demand for transparency in the adaptation of political messages, coupled with apprehension towards personalised content, highlighting privacy and manipulation concerns. The research shows divided opinions on the necessity of stringent regulations for targeted political ads, yet there is broad agreement on the importance of disclosing advertising sources and labelling ads clearly to enhance awareness. The study also reveals that most respondents feel they have limited control over the content they encounter online, though a minority report feeling more in control than the content providers. Furthermore, by employing multinomial regression analysis, the paper finds age, gender, and education as key predictors influencing perceptions of potential risks related to personalised political advertising. This investigation sheds light on the complexities of digital personalisation in political communication, offering insights for future policy and regulation.